Aspects of wellness in a traditional leisure time game: an integrated approach for teaching innovation / Mawarni Mohamed and Puteri Aquila Tajuddin. - Mohamed, Mawarni; Tajuddin, Puteri Aquila (2018)
Malaysia and ASEAN society are rich with a variety of traditional games and usually played during leisure time. 'Tossing the Stones' or Batu Seremban was chosen in this survey. Using a purposive sampling technique, respondents from Malaysia, Philippines, Indonesia and Thailand went through the game intervention and answered the questionnaires provided. The goal was to understand how they perceived wellness while playing this game, after identifying the frequency of Traditional Games engagement. Results showed that Batu Seremban gave high wellness scores such as; M=4.16, SD=.722. The physical, intellectual, social and emotional elements identified in 'Tossing the Stones' showed that strong educational elements identified in the traditional leisure game can also be used to teach children and young adults through integration in the curriculum. Suggestions on how the game can be used in classrooms were made based on the findings.